-3(-2x + 9)
= (-3) x (-2x) + (-3) x 9
= 6x -27
2006-09-28 07:02:16
·
answer #1
·
answered by buaya123 3
·
0⤊
0⤋
Just multiply the -2x by the -3 and then the 9 by the -3.
-3(-2x + 9)
6x - 27
2006-09-28 14:03:25
·
answer #2
·
answered by John 1
·
0⤊
0⤋
I think it goes like this -3*-2x + -3*9= 6x - 27 6x=27 /6 x=4.5
2006-09-28 14:04:47
·
answer #3
·
answered by Banna_skillz 2
·
0⤊
1⤋
You said show work, right?
-3(-2x + 9) is equal to -3 x -2x ~ (neg time neg = pos)
and -3 x 9 (neg time pos = neg)
(6x + 27)
Clear?
2006-09-28 14:10:11
·
answer #4
·
answered by Persephone 2
·
0⤊
0⤋
-3(-2x + 9)
= -6x + 27
i think this is how u jus times -3 wid the numbers in the brackets
hope it helps
2006-09-28 14:15:18
·
answer #5
·
answered by sandhya p 1
·
0⤊
0⤋
-3*-2x = 6x
-3*9= -27
so therefore you get 6x-27 when you distribute
2006-09-28 14:02:27
·
answer #6
·
answered by mjb1285 1
·
0⤊
0⤋
-3*-2x + -3 *9
=6x - 27
you just multiply what is outside the parenthesis with everything that is inside the parenthesis
2006-09-28 14:02:17
·
answer #7
·
answered by Me 3
·
0⤊
0⤋
-3(-2x + 9)
= (-3) x (-2x) + (-3) x 9
= 6x -27
2006-09-28 14:07:03
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
-3(-2x+9)
= 6x-27
6x=27
x=27/6
2006-09-28 14:04:29
·
answer #9
·
answered by Fred K 3
·
0⤊
0⤋
-3(-2x + 9)
6x-18
2006-09-28 14:07:39
·
answer #10
·
answered by Emo Girl 2
·
0⤊
0⤋